2004
DOI: 10.1002/ajim.20019
|View full text |Cite
|
Sign up to set email alerts
|

Vibration exposure and disease in a shipyard: A 13‐year revisit

Abstract: The prevalence of vascular symptoms associated with cumulative vibratory exposure was significantly greater in 1988, but neurological symptoms were more common at lower exposure levels in 2001. The presumption that reducing exposure duration alone is sufficient, in the absence of change in vibration magnitude, is not supported by the results of this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…The reported prevalence is high compared with that of unexposed male workers in the general population, for which the point prevalence has been reported to be <5% (9) for vascular symptoms and 15% (19) for neurological symptoms. The prevalence of vascular symptoms among the workers is in agreement with that for other vibration-exposed groups (9), and, moreover, the result agrees with those of other studies in which a higher prevalence was also found for neurological symptoms (20)(21)(22). The development of symptoms shows that, within the first 10 years of work with vibration handheld tools, 30% of the cohort had experienced their first symptoms (either vascular or neurological).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The reported prevalence is high compared with that of unexposed male workers in the general population, for which the point prevalence has been reported to be <5% (9) for vascular symptoms and 15% (19) for neurological symptoms. The prevalence of vascular symptoms among the workers is in agreement with that for other vibration-exposed groups (9), and, moreover, the result agrees with those of other studies in which a higher prevalence was also found for neurological symptoms (20)(21)(22). The development of symptoms shows that, within the first 10 years of work with vibration handheld tools, 30% of the cohort had experienced their first symptoms (either vascular or neurological).…”
Section: Discussionsupporting
confidence: 90%
“…This finding suggests that vibration magnitude plays a significant role in the prediction of symptoms, and it highlights the necessity for correct vibration exposure estimates. The differences in the correlation between the two types of symptoms could be due to the fact that vascular symptoms tend to be more specific to exposure to hand-arm vibration than neurological complaints since the latter can also originate from other nonvibratory causes, such as biomechanical risks (20).…”
Section: Discussionmentioning
confidence: 99%
“…Increased prevalence or excess risk for neurosensory disturbances, CTS and/or abnormal sensory testing have been reported in crosssectional studies of HTV-exposed workers carried out in several countries (19)(20)(21). Only few studies have investigated prospectively the occurrence of neurosensory disorders in HTV-exposed workers.…”
Section: Exposure-response Relationship For Vibration-induced Sensorymentioning
confidence: 99%
“…Typically accurate cumulative vibration exposures are achieved in longitudinal studies like Suomussalmi forest worker study (Sutinen et al 2006) or submarine worker study (Cherniack et al 2004). In cross-sectional studies the vibration levels cannot be determined accurately, especially for previous instruments.…”
Section: Discussionmentioning
confidence: 99%